Transgressing theory/practice divides through collaboration. : Building research communities with professionals - Kousholt, Dorte; Højholt, Charlotte (Outlines. Critical Practice Studies, 2023)
This article contributes to discussions of transmethodology by drawing on experiences from conducting practice research aimed at the development of theory and practice through research collaboration. We analyze efforts to build research communities where researchers and professionals work together to perform analyses and develop knowledge. A collective research project exploring children’s possibilities for participation in school is used as a case for exploring how a research problem develops through such collabora-tion. This research project was designed to explore school life from the perspectives of children, parents, teachers, school leaders, and psychologists, and to analyze conflicts situated in everyday practices while considering political struggles concerning the school as a historical institution. The article emphasizes the often intangible and overlooked processes involved in research collaboration and details how we worked to build a re-search community comprising researchers and professionals that enabled collective mul-ti-perspective analyses. Building on a dialectical approach, we conceptualize conflicts as part of historical processes and as an immanent potentiality that arises from people’s engagement in common but contradictory matters. Hence, the different perspectives of those involved in children’s school life can be seen as linked through common matters, while also being differentiated by their allotted tasks in relation to children’s school life. This approach continuously challenged the researchers to analyze everyday conflicts grounded in the different perspectives of those involved, the different forms of reasoning, understandings, and standpoints, as well as how the different perspectives are connected through the participants’ engagement in a common matter – providing good schools for children. The article concludes by arguing that the discussed approach to theory devel-opment can be linked to a situated concept of generalization.